2002
DOI: 10.1073/pnas.062066299
|View full text |Cite
|
Sign up to set email alerts
|

A common mutation in the 5,10-methylenetetrahydrofolate reductase gene affects genomic DNA methylation through an interaction with folate status

Abstract: DNA methylation, an essential epigenetic feature of DNA that modulates gene expression and genomic integrity, is catalyzed by methyltransferases that use the universal methyl donor S-adenosyl-L-methionine. Methylenetetrahydrofolate reductase (MTHFR) catalyzes the synthesis of 5-methyltetrahydrofolate (5-methyl-THF), the methyl donor for synthesis of methionine from homocysteine and precursor of S-adenosyl-L-methionine. In the present study we sought to determine the effect of folate status on genomic DNA methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
625
7
13

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 835 publications
(679 citation statements)
references
References 62 publications
34
625
7
13
Order By: Relevance
“…Using our Mthfrdeficient mouse model, we demonstrated directly that disruption of the Mthfr gene or low dietary folate adversely affect the developing heart [1]. This finding is likely related to the fact that MTHFR deficiency in humans and mice is associated with low methylTHF, high homocysteine and reduced DNA methylation [21][22][23].…”
Section: Introductionmentioning
confidence: 77%
“…Using our Mthfrdeficient mouse model, we demonstrated directly that disruption of the Mthfr gene or low dietary folate adversely affect the developing heart [1]. This finding is likely related to the fact that MTHFR deficiency in humans and mice is associated with low methylTHF, high homocysteine and reduced DNA methylation [21][22][23].…”
Section: Introductionmentioning
confidence: 77%
“…This is counterintuitive because uracil in DNA is positively correlated with MNBN in other studies using this system (Crott et al, 2001). However, MNBN may originate not only from chromosome breakage caused by uracil in DNA, but also from chromosomal loss events that may be caused by hypomethylation of DNA (Friso et al, 2002). One study reported that the 677TT with a mutated 1298 locus genotype increases DNA hypomethylation in lymphocytes in vivo (Campbell et al, 2002), and DNA hypomethylation in lymphocytes in vitro or in vivo increases the loss of chromosomes 1, 9 and 16, which are then included in MNBN (Guttenbach et al, 1994;Xu et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in vivo experiments in humans, such as examination of the effect of gene polymorphisms [6] and nutritional status [6,7] on DNA metabolism, have used labeled one-carbon donors to label monocyte DNA. Nucleoside hydrolysates of DNA also have been used in determining the base composition of DNA, including investigation of epigenetic modification such as deoxycytosine methylation [8,9], oxidative damage [10,11], or unique DNA composition [12].…”
Section: Introductionmentioning
confidence: 99%